Enhancing ICT for quality education in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This research assesses the relevance of information and communication technology (ICT) in primary education quality in a panel of 49 Sub-Saharan African countries for the period 2000-2012. The empirical evidence is based on Two Stage Least Squares (2SLS) and Instrumental Quantile regressions (IQR). From the 2SLS: (i) mobile phone and internet penetration rates reduce poor quality education and enhancing internet penetration has a net negative effect o f greater magnitude. From the IQR: (i) with the exception of the highest quantile for mobile phone penetration and top quantiles for internet penetration, ICT consistently has a negative effect on poor education quality with a non-monotonic pattern. (ii) Net negative effects are exclusively apparent in the median and top quantiles of internet-related regressions. It follows that enhancing internet penetration will benefit countries with above-median levels of poor education quality while enhancing internet penetration is not immediately relevant to reducing poor education quality in countries with below-median levels of poor education quality.
Keywords: F24; F63; L96 O30; O55; 330; CT; Primary school education; Development; Sub-Saharan Africa